A rare case of heterotopic pregnancy: case report - Patel, Nisi; Patel, Komal; Shah, Bipin R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Heterotopic pregnancy is defined as the coexistence of intrauterine and extrauterine gestation. The incidence is low and estimated to be 1 in 30,000 of spontaneous pregnancies though it is becoming commoner with assisted reproductive technique. It can be a life-threatening condition and can be easily missed with the diagnosis being overlooked. We present a rare case of spontaneous heterotopic pregnancy with intrauterine gestation without cardiac activity and unruptured tubal ectopic.